Connectivity as a multiple: In, with and as "nature". Issue 1 (24th May 2017) - Hodgetts, Timothy
Abstract : Connectivity is a central concept in contemporary geographies of nature, but the concept is often understood and utilised in plural ways. This is problematic because of the separation, rather than the confusion, of these different approaches. While the various understandings of connectivity are rarely considered as working together, the connections between them have significant implications. This paper thus proposes re‐thinking connectivity as a "multiple". It develops a taxonomy of existing connectivity concepts from the fields of biogeography and landscape ecology, conservation biology, socio‐economic systems theory, political ecology and more‐than‐human geography. It then considers how these various understandings might be re‐thought not as separate concerns, but (following Annemarie Mol) as "more than one, but less than many". The implications of using the connectivity multiple as an analytic for understanding conservation practices are demonstrated through considering the creation of wildlife corridors in conservation practice. The multiple does not just serve to highlight the practical and theoretical linkages between ecological theories, social inequities and affectual relationships in more‐than‐human worlds. It is also suggestive of a normative approach to environmental management that does not give temporal priority to biological theories, but considers these as always already situated in these social, often unequal, always more‐than‐human ecologies.